May day merrymaking & munchies - Anderhagen, Anna (Abdo Group, 2024)
This book is full of May Day jokes and recipes for tasty treats, such as Sweet Butterflies and May Day Candy Pizza. Jokes, puns, one-liners, and riddles accompany the recipes in bursts on each page, which adds just the right amount of humor! So, celebrate the day with merrymaking and munchies